Pengaruh Disiplin, Motivasi, Budaya Organisasi Dan Stres Terhadap Kepuasan Kerja Pendidik Di Kabupaten Brebes - Sulaefi Sulaefi (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2018)
This is researchaims to influenceof work discipline, motivation, organizational culture, and work stress on public teacher’s job satisfaction at the Public High School at Brebes District. This research was conducted in four Public High School. Primary data by the method of survey with questionnaires from 100 responden to the scale Likert with hypothesis used this research. The techniques of processing and analysis data used linear regression analysis. Resultof the analysis performed revealed that there are positive effect of variable work discipline of teacher ‘s job satisfaction positive influence motivational variable of teacher’s job satisfaction, positive influence on organizational culture variables jobsatisfaction of the teacher, negative effect of work stress variables on teachers job satisfaction and positive influence of work discipline, motivation, and organizaonal culture stress work simultaneously on teacher’ job satisfaction.